Investigating BB0405 as a novel Borrelia afzelii vaccination candidate in Lyme borreliosis - Klouwens, M J; Trentelman, J J; Ersoz, J I; Nieves Marques Porto, F; Sima, R; Hajdusek, O; Thakur, M; Pal, U; Hovius, J W (Scientific reports, 2021)
BB0405 is a surface exposed Borrelia burgdorferi protein and its vaccination protected mice against B. burgdorferi infection. As BB0405 is highly conserved across different B. burgdorferi sensu lato species, we investigated whether vaccination with recombinant BB0405 or through intradermal bb0405 DNA tattoo vaccination could provide protection against different Borrelia species, specifically against Borrelia afzelii, the predominant B. burgdorferi sensu lato genospecies causing Lyme borreliosis across Eurasia. We immunized C3H/HeN mice with recombinant BB0405 or with a codon-optimized bb0405 DNA vaccine using the pVAC plasmid and immunized corresponding control groups mice with only adjuvant or empty vectors. We subsequently subjected these immunized mice to a tick challenge with B. afzelii CB43-infected Ixodes ricinus nymphs. Upon vaccination, recombinant BB0405 induced a high total IgG response, but bb0405 DNA vaccination did not elicit antibody responses. Both vaccine formulations did not provide protection against Borrelia afzelii strain CB43 after tick challenge. In an attempt to understand the lack of protection of the recombinant vaccine, we determined expression of BB0405 and showed that B. afzelii CB43 spirochetes significantly and drastically downregulate the expression of BB0405 protein at 37 °C compared to 33 °C, where as in B. burgdorferi B31 spirochetes expression levels remain unaltered. Vaccination with recombinant BB0405 was previously shown to protect against B. burgdorferi sensu stricto. Here we show that vaccination with either recombinant BB0405 (or non-immunogenic bb0405 DNA), despite being highly conserved among B. burgdorferi sl genospecies, does not provide cross-protection against B. afzelii, mostly likely due to downregulation of this protein in B. afzelii in the mammalian host.
Keywords: Recombinant Proteins; Borrelia burgdorferi komplex; Borrelia burgdorferi; lymeská nemoc; Bacterial Outer Membrane Proteins; Lyme Disease Vaccines; Mice, Inbred C3H; Lyme Disease; imunogenicita vakcíny; vakcína proti lymeské nemoci; Borrelia burgdorferi Group; myši inbrední C3H; rekombinantní proteiny; Animals; ženské pohlaví; zvířata; tvorba protilátek; myši; Antibody Formation; Immunogenicity, Vaccine; Mice; Female; DNA vakcíny; Vaccines, DNA; proteiny vnější bakteriální membrány